Child Development in Parent-Child Interactions - Seror, Avner (Journal of Political Economy, 2022)
I present a model of child development that highlights the effect of parent-child interactions on the formation of skills. Through the parent’s affection, the child learns and builds mental representations of the self as loved and competent. These mental representations shape the child’s noncognitive skills and foster learning. I show that this model provides a unifying explanation for well-established evidence on child development. The model also sheds light on how early exposure to media devices can negatively impact skill acquisition. I discuss implications for the design of policies to reduce inequalities in child development.